How to Have a Home Garden! Problems and Solutions: Qatif Case Study - Elantary, Asmaa Ramadan; Aldubaisi, Fatimah Fadhel; Alasif, Zahra Abdulrouf (Journal of agricultural, environmental and veterinary sciences, 2021)
Removing home gardens from most of the current houses, meanwhile, converting farms or parts of them into residential. This is a big problem that this study aims to explore the causes that residents face and push them to remove home gardens, and to find solutions to help them preserve them. A questioner was published, and 180 responses were received. The responses varied between those who inhabit different types of housing (apartment or house), (owned or rented). The reasons were divided into four main problems (living in an apartment, less agricultural knowledge, difficulty in cleaning garden and preferring artificial garden). Which indicated that housing in an apartment is one of the most important reasons, with an average of 3.57 on the five-point Likert scale. Likewise, the artificial garden is preferred, with an average of 3.43, due to the other activities and time of interest required by cultivation. To solve these problems, the research suggested allocating a common garden sometimes, as well as providing a table for plants suitable for growth in Qatif, which includes the name of the plant, the type of fertilizer, the time of fertilization, and the amount of sunlight needed. The preference for owning artificial home gardens was puzzling, as the results were counter-productive, and despite their preference for them because of their busyness, they do not prefer to own them instead of natural gardens.